The Cyanobacterium Cylindrospermopsis raciborskii (CYRF-01) Responds to Environmental Stresses with Increased Vesiculation Detected at Single-Cell Resolution - Zarantonello, Victor; Silva, Thiago P.; Noyma, Natália P.; Gamalier, Juliana P.; Mello, Mariana M.; Marinho, Marcelo M.; Melo, Rossana C. N. (Frontiers in Microbiology, 2018)
Secretion of membrane-limited vesicles, collectively termed extracellular vesicles (EVs), is an important biological process of both eukaryotic and prokaryotic cells. This process has been observed in bacteria, but remains to be better characterized at high resolution in cyanobacteria. In the present work, we address the release of EVs by Cylindrospermopsis raciborskii (CYRF-01), a filamentous bloom-forming cyanobacterium, exposed to environmental stressors. First, non-axenic cultures of C. raciborskii (CYRF-01) were exposed to ultraviolet radiation (UVA + UVB) over a 6 h period, which is known to induce structural damage to this species. Second, C. raciborskii was co-cultured in interaction with another cyanobacterium species, Microcystis aeruginosa (MIRF-01), over a 24 h period. After the incubation times, cell density and viability were analyzed, and samples were processed for transmission electron microscopy (TEM). Our ultrastructural analyses revealed that C. raciborskii constitutively releases EVs from the outer membrane during its normal growth and amplifies such ability in response to environmental stressors. Both situations induced significant formation of outer membrane vesicles (OMVs) by C. raciborskii compared to control cells. Quantitative TEM revealed an increase of 48% (UV) and 60% (interaction) in the OMV numbers compared to control groups. Considering all groups, the OMVs ranged in size from 20 to 300 nm in diameter, with most OMVs showing diameters between 20 and 140 nm. Additionally, we detected that OMV formation is accompanied by phosphatidylserine exposure, a molecular event also observed in EV-secreting eukaryotic cells. Altogether, we identified for the first time that C. raciborskii has the competence to secrete OMVs and that under different stress situations the genesis of these vesicles is increased. The amplified ability of cyanobacteria to release OMVs may be associated with adaptive responses to changes in environmental conditions and interspecies cell communication.